Pet velikih faktorjev osebnosti - Bucik, Valentin (Psihološka obzorja (Ljubljana), 1995)
Last five years gave a full swing to the research of personality. The results of both lexicographic and factor-analytic studies showed that the structure of personality converges toward the five factors (the so called "Big Five" model - BFM). By stepwise analyses of 4500 Allport's and Odbert's adjectives Cattell (1943) reached 12 personality factors that were the base ofhis personality-traits theory. The fact that Cattell's Dimensions rest on the BFM was confirmed in reanalyses of his data performed by other autors. Two branches of research were developed from the Cattell's practice: (a) Norman (1967) shelled 75 common traits, from the base of 18000 personality=traits descriptions, and Goldberg (1981, 1983) extracted five factors out of them; (b) Peabody and Goldberg (1989) confirmed the BF structure from the variables which served completely different model of personality. According to BFM the five principal factors are: Energy (extroversion, surgency), Friendliness (emotional support, kindness, affection), Conscientiousness (reliability), Emotional stability (neuroticism)and Openness (mental openness, intellect). In USA Costa and McCrae (1992) developed a questionnaire NEO-PI-R, which rests on the BF model,and in Europe the similar questionnaire was created a year later (Big Five Questionnaire - Caprara, Barbaranelli & Borgogni, 1993). It was translated into Spanish and English language and there are French, Dutch, German, Polish and Slovenian versions in praparation. The rating scale (Big Five Observer), which enables us to estimate ourselves or others on the list of 40 bipolar adjectives, is also attached to the questionnaire.
Keywords: osebnost; personality; psihologija osebnosti; psihološki testi; model velikih pet